Predators and Parasitoids-in-First: From Inundative Releases to Preventative Biological Control in Greenhouse Crops - Pijnakker, Juliette; Vangansbeke, Dominiek; Duarte, Marcus; Moerkens, Rob; Wäckers, Felix L. (Frontiers in Sustainable Food Systems, 2020)
Repeated mass introductions of natural enemies have been widely used as a biological control strategy in greenhouse systems when the resident population of natural enemies is insufficient to suppress the pests. As an alternative strategy, supporting the establishment and population development of beneficials can be more effective and economical. The preventative establishment of predators, before the arrival of pests, has become a key element to the success of biological control programs. This “biocontrol-in-first” strategy is used both in Inoculative Biological Control (IBC), and in Conservation Biological Control (CBC). Here, we provide an overview of tools used to boost resident populations of biocontrol agents.